Konstruktna veljavnost Testa implicitnih asociacij za merjenje velikih pet - Zager Kocjan, Gaja (Psihološka obzorja (Ljubljana), 2013)
Psychology has recently seen a noticeable increase in interest for implicit measures of attitudes and personality characteristics. The far most known implicit measure is the Implicit Association Test - IAT. We adapted this test in order to assess the Big Five personality dimensions (B5 IAT). We examined B5 IAT measurement characteristics on two samples. Based on the findings of the first sample (N = 62), improvements were made in the B5 IAT, to be tested again on another sample (N = 75). The two studies have shown similar results. The reliabilities of the personality dimensions measured with the B5 IAT failed to achieve a satisfactory level in most cases. The reason probably lies in a lower adequacy of certain stimuli and in the considerable length of the test procedure. The convergent validity of the B5 IAT with explicit measures of personality was low, which may be due to different structures underlying implicit and explicit measures. Results obtained on the first sample have shown that the correlations between IAT adjectives are adequately explained by five latent dimensions. However, these results should be interpreted with caution due to B5 IAT low reliabilities and small sample sizes. The second sample proved to be very unstable, thus the confirmatory factor analysis could not be conducted. Since this is the first attempt to adapt B5 IAT to Slovene language, it is hardly surprising that the results are not entirely consistent with the expectations. As implicit measures currently fail to meet relevant psychometric characteristics, they are not yet applicable in psychological practice. Nevertheless, they have great potential in exploring personality and individual differences, as they overcome many limitations of existing explicit measures.
Keywords: osebnostne lastnosti; personality traits; petfaktorski model osebnosti; five factor personality model; attitudes; stališča; implicit measures; implicitne mere; merske značilnosti; metric characteristics; konstruktna veljavnost; construct validity; Implicit association test IAT; Test implicitnih asociacij IAT